Ionically conductive materials, electrolytes including ionically conductive materials, and methods of forming same - Patents.com
By performing solid phase reaction at a lower temperature, using cesium amide salt and metal oxide as starting materials, the composite metal halide electrolyte material is formed, which solves the problems of high production cost and poor stability of solid electrolyte materials in the prior art, and achieves the production of electrolyte materials with high purity, low cost and high conductivity.
Patent Information
- Application Number
- JP2023173805
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-14
- Filing Date
- 2023-10-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-04-14
AI Technical Summary
Existing solid electrolyte materials have challenges in safety, chemical and electrochemical stability, and large-scale production costs, especially high costs and high pollution caused by high temperature synthesis and high energy ball milling.
A new process is adopted to form a composite metal halide electrolyte material by performing solid phase reactions at lower temperatures using cesium amide salts and metal oxides as starting materials, and synthesize them by a one-step process to reduce costs and improve purity.
It realizes the production of high-purity and low-cost solid electrolyte materials, improves the conductivity and electrochemical stability of the materials, and reduces environmental pollution during the production process.
Smart Images

Figure 0007654321000005 
Figure 0007654321000006 
Figure 0007654321000007
Abstract
Description
[Technical Field]
[0001] Technical Field The following describes a solid ion-conductive material, an electrolyte containing the ion-conductive material, and a method for forming the same: In particular, a solid ion-conducting material containing a complex metal halide, an electrolyte containing the same, and a method for forming the same. [Background technology]
[0002] Background technology Solid-state lithium batteries use lithium metal as the negative electrode, which is different from conventional lithium-ion batteries. Compared to conventional batteries, they are expected to have higher energy density, shorter charging times, and fewer safety concerns. Current solid electrolyte materials include oxides, halides, sulfides, fluorides, solid polymers, and These include:
[0003] Oxide-based materials have been considered to be highly safe and have good chemical and electrochemical stability. The synthesis of these compounds generally involves high temperatures exceeding 1000-1200°C. Oxide materials are generally dense, hard, and brittle, with a maximum ionic conductivity of 1.0 mS / cm (IC RT ).
[0004] Halide compounds such as chlorides and bromides are generally safe and are chemically and electrochemically It has good chemical stability, deformability, and plasticity, and allows for relatively high compatibility with electrode active materials. In Li3YCl6 (LYC) and Li3YBr6 (LYB) electrolytes, the cm or higher ionic conductivity IC RT Halides are generally hygroscopic. When exposed to moisture, they form hydrates or undergo hydrolysis. Such halide-based solid electrolytes have been synthesized by a solid-state synthesis method using high-energy ball milling. However, it requires expensive binary halide reactants and high-temperature annealing, which makes it difficult to synthesize large-scale Mass production presents challenges.
[0005] Fluorides are very similar to oxides in physical, chemical, and electrochemical properties, but , generally IC RT The value is less than 1 mS / cm.
[0006] Sulfides have relatively high ionic conductivity. For example, IC RT High at 25mS / cm Commercially relevant sulfide or thiophosphate solid electrolytes achieve 2-10 mS / cm. Sulfide-based materials are mechanically soft and easily deformed. tend to have poor electrochemical stability and react inadvertently with water and heat to release toxic H2S gas There are safety concerns due to the risk of sulfide solid electrolyte powders with high surface area. , and the risk of H2S is particularly high because it is highly reactive even in humid conditions.
[0007] Generally, solid polymer electrolytes containing lithium salts have relatively low ICRT values and electrochemical stability. Low target.
[0008] The industry continues to demand improved solid electrolyte materials. [Brief explanation of the drawings]
[0009] BRIEF DESCRIPTION OF THE DRAWINGS The present disclosure may be better understood and its numerous features and advantages may be better understood by reference to the accompanying drawings. The advantages and benefits will be apparent to those skilled in the art. [Figure 1] FIG. 1 includes a flow chart illustrating steps for forming a solid, ionically conductive material according to an embodiment. [Figure 2] FIG. 2 includes a flow chart illustrating steps for forming a solid, ionically conductive material according to another embodiment. [Figure 3] Figure 3A includes a cross-sectional illustration of a solid, ionically conductive material according to an embodiment, and Figure 3B includes an illustration showing an exemplary crystallographic orientation of the solid, ionically conductive material of Figure 3A. [Figure 4] FIG. 4 includes a flow chart illustrating steps for forming a solid, ionically conductive material according to an embodiment. [Figure 5] FIG. 5 includes an explanatory cross-sectional view showing a part of the solid state battery according to the embodiment.
[0010] Skilled artisans will appreciate that elements in the figures are illustrated for simplicity and clarity and are not necessarily drawn to scale. For example, the dimensions of some elements in the figures are not necessarily accurate to the present invention. The dimensions of elements may be exaggerated relative to other elements to help understand the embodiments. The use of the same reference numbers indicates similar or identical items. DETAILED DESCRIPTION OF THE INVENTION
[0011] Detailed Description of the Preferred Embodiments The following description in conjunction with the figures will aid in understanding the teachings disclosed herein. The following discussion focuses on specific implementations and embodiments of the present teachings. The focus is provided to help explain the teachings and to limit the scope or applicability of the teachings. should not be construed as such.
[0012] As used herein, the terms "comprise," "include," "includes," "having," " "having," "having," or other variations thereof, is intended to cover a non-exclusive inclusion. For example, a process, method, article, or apparatus that includes a list of features does not necessarily include those features. This includes, but is not limited to, any other features or characteristics not expressly listed. It may include process, method, article, or apparatus specific features. Unless expressly stated to the contrary, "or" refers to an inclusive "or" and not an exclusive "or." For example, condition A or B can be satisfied by one of the following: For example, condition A or B can be expressed as A is true (or exists), B is false (or does not exist), and A is false. (or does not exist), B is true (or exists), A and B are both true (or exist) It is fulfilled by one of the following:
[0013] The use of "one" or "one" describes elements and components described herein. This is merely for convenience and to give a general sense of the scope of the invention. This specification, unless otherwise clear, refers to one or more should be read to include at least one, and the singular also includes the plural and vice versa. The same is true.
[0014] Unless otherwise defined, all technical and scientific terms used herein are within the meaning of the present invention. has the same meaning as commonly understood by a person of ordinary skill in the art The materials, methods, and examples are illustrative only and not intended to be limiting.
[0015] Embodiments herein relate to solid, ionically conductive materials comprising complex metal halides, The group can include at least one alkali metal element. In one embodiment, the solid ion The ion-conducting material may include a dopant comprising ammonium. , the solid ionically conductive material is a crystalline material, and in certain embodiments, a material having a particular crystallographic orientation. The solid state material may include oriented crystalline materials such as single crystals or oriented ceramics having a Ion conductive materials have advantages over conventional metal halide materials in purity, bulk ionic conductivity, , electrochemical stability, or any combination thereof. In embodiments, the solid, ionically conductive material can be an electrolyte, an anode, and / or can be used to form a cathode, or another component of an electrochemical device. In certain embodiments, the solid, ionically conductive material is a suitable component of a solid-state lithium battery. It can be said that:
[0016] Embodiments relate to a method for forming an ionically conductive material, the method comprising the steps of: Ions having improved properties such as conductivity, electrochemical stability, or a combination thereof. The method can also allow for the formation of ion-conducting materials. This method can provide improved ion-conducting materials in a cost-effective manner. It may be suitable for mass production of materials.
[0017] Referring to FIG. 1, a process for forming a solid, ionically conductive material 100 is shown. .
[0018] Process 100 differs from conventional solid-state syntheses for forming complex metal halides. Conventional processes utilize high energy ball milling or Compounds (e.g., simple metal halides) at or below the melting point of the metal halide The reaction is carried out by directly heating the mixture at a temperature of 1000°C. As the reaction progresses, the probability of reaction decreases, so theoretically, 100.00% reaction completion is It is thought that this would take an infinite amount of time. The reaction products obtained in the synthesis are simple metal halides (e.g., lithium halides and The reaction of yttrium halide and / or yttrium halides is incomplete, resulting in high impurity concentrations. It is understood that
[0019] More notably, conventional complex halogenation based on the ammonium-halide route The synthesis of metal halides may not be applicable to the formation of complex metal halides. Halides of trivalent and tetravalent metals are traditionally used as starting materials. In particular, rare earth metal halides tend to form stable metal halide hydrates. It may be difficult to completely remove water molecules from the material, so trivalent metal halides are used. As the temperature increases, undesirable metal oxyhalides and metal oxy Halide compounds of hydrates can be formed in high concentrations. Halide hydrates and metal oxyhalides, especially those containing rare earth metals, are rather cheap. The specific compound is Li3RE(OX)Cl3, where X is a halogen other than Cl. It is unlikely that a complex compound phase containing such a high concentration of Li will form. The compound is not stable and is likely to decompose into simpler compounds.
[0020] The process described in the embodiments of the present disclosure overcomes the above-mentioned problems.
[0021] Process 100 may begin at block 102. A reaction mixture containing starting materials is formed. In embodiments, the starting material is an ammonium halide, NH4X. X may include Cl, Br, I, F, or any combination thereof. The material may further comprise one or more metal compounds, the metal being an alkali element, an alkali metal, or a metal compound. containing lithium earth elements, transition metal elements, lanthanides, rare earth elements, or any combination thereof. It can be done.
[0022] In certain embodiments, the metal compound may be non-hygroscopic. Compounds include oxides, carbonates, sulfates, hydrates, hydroxides, oxalates, acetates, nitrates, or any combination thereof. Thus, the starting material can include one or more metal oxides. For example, the starting material can include Me 2O k where Me is a divalent metal, a trivalent metal, a tetravalent metal, a pentavalent metal, k is the valence of the metal; and 2≦k≦6. In particular examples, Me can be selected from Ce, Dy, Er, Eu, Gd, Ho, La, L u, Nd, Pr, Pm, Sm, Sc, Tb, Tm, Yb, Sc, and Y, In, Zn, Alkali metal elements, rare earth elements such as Hf, Zr, or any combination thereof In a more specific example, the starting material may include a rare earth oxide or hydroxide or is carbonate, ZrO2 or Zr(OH)4 or Zr(CO3)2 or Zr(OH)2 The compound may comprise one or more of CO3·ZrO2 or any combination thereof.
[0023] In another embodiment, the starting material is lithium carbonate, sodium carbonate, cesium carbonate, or the like. The starting material may include an aqueous solution, an alkali metal compound, or a combination thereof. To facilitate acid synthesis in alcohol or other polar molecular liquid solutions, the acid is further It can include.
[0024] In another particular example, the metal compound can include an alkali metal compound. The starting materials are alkali metal halides (e.g., NaCl, CsCl, and LiCl). and may not include compounds containing Me.
[0025] In embodiments, the starting materials may be mixed in stoichiometric ratios. The ratio between the activators can allow the formation of non-stoichiometric complex metal halides. do.
[0026] In an exemplary embodiment, NH4X, one or more rare earth metal oxides (hereinafter "RE2 A reaction mixture containing HCl, HCl, and HCl is formed. The starting materials and reaction products in aqueous solution are shown below, along with an example of the reaction. 3 * Li2CO3+ RE2O3+ 12 * HX+ 6 * NH4X ---> 2 * (NH4)3REX6+ 6 * LiX + 6 * H2O+ 3 * CO2
[0027] The above reactions are examples intended to aid in understanding process 100. From this point of view, one skilled in the art would be able to determine whether another alkali metal compound such as Na2CO3 or NaCl is the starting material. Similarly, oxides of non-rare earth elements, such as Fe2 O3 may be added to the reaction. Those skilled in the art will further understand that if the starting materials change, the reaction products may also change accordingly.
[0028] In certain embodiments, Process 100 can include chemically substituting water (i.e., water) in a hydrated salt containing MeX k with NH4X. In one aspect, the process can include forming (NH4) Me X n where n > 0; and 2 ≤ k < 6). In certain embodiments, 0 < n ≤ 3. In certain examples, n k+ X n+k can be 0.33, 0.5, 1, 1.5, 2, 3, or 4, depending on what Me is. In the above-exemplified reaction, a hydrated rare earth halide may be formed as an intermediate product, and the water in the hydrate is replaced with NH4X to form an advantageous non-forming hydrate compound ([(NH4)3REX6]), allowing the operation and maintenance of a hydroxide-free halide phase. Further exemplified, an alkali metal halide such as LiX is also formed.
[0029] In one example, the mixture of reaction products may be filtered to remove larger particles to facilitate subsequent reactions in the solid state. Larger particles can include impurities associated with any of the starting materials, residual particles of the starting materials, carbon, or any combination thereof.
[0030] Process 100 can continue to Block 104. In embodiments, the mixture of reaction products is (NH4) Me n X k+ and an alkali metal halide, MX ( n+k where M is an alkali metal element) can be dried to facilitate solid-state reaction. Drying may be carried out in air or dry air and / or under vacuum or reduced pressure, e.g., at 100 mbar. It can be carried out at 1 mbar, 40 mbar, 1 mbar, or 0.01 mbar. In some instances, N2 or Ar flow may be used to aid in the removal of moisture. In this example, heat may be applied to aid in the evaporation of water. The heating temperature is 100°C to 160°C. ° C. Drying may leave a trace amount of water, e.g., 1 wt% to 3 wt%, in the mixture. It may be performed up to.
[0031] In an embodiment, the process 100 comprises: n Me k+ X n+k and MX solids In a particular example, the reaction may include reacting the above reaction product with (NH4)3R The solid-state reaction of EX6 and LiX can be carried out. In another embodiment, the process 100 is (NH4) n M 3-z Me k+ X 3+n+k-z forming a Here, -3≦z=<3. When z=0, (NH4) n M 3-z Me k+ X 3+n+k -z is stoichiometric. When z is not 0, (NH4) n M 3-z Me k+ X 3+n +k-z is non-stoichiometric. In particular examples, 0≦z<1. In further examples, The 100th degree is M 3-z (Me k+ ) f X 3-z+k*fwherein -3≦z<3; 2≦k<6; 0≦f≦1.
[0032] Process 100 may continue to block 106. In an embodiment, Forming the ammonium conductive material can include decomposing an ammonium halide. In one embodiment, the decomposition is from an ammonium halide phase to a complex metal halide phase. In another aspect, forming the ionically conductive material can include separating , which may further include elimination of ammonium halide.
[0033] In one embodiment, the decomposition is carried out in a crucible made of a material inert to the reactants and products. For example, the crucible may be made of quartz, alumina, silica-alumina, BN, or gallium. It may be made of lath carbon or graphite. The sheet may have a coating of pyrolytic carbon.
[0034] In another embodiment, the decomposition may be carried out in a dry, neutral atmosphere, such as air or dry air. An inert gas such as N2 or Ar may be used to facilitate the process.
[0035] In further embodiments, the degradation may be carried out for at least 15 minutes and up to 24 hours. In an embodiment, the solid solution is heated to a temperature in the range of 350° C. to 800° C. to form an aryl halide. In some embodiments, the N The sublimation of H4X is monitored by weighing the escaped NH4X, which is collected and condensed on the other side. It can be viewed.
[0036] In a further embodiment, a small amount of ammonium halide is added relative to the weight of the ammonium halide initially added. at least 60 wt%, at least 80 wt%, or at least 90 wt% halogenated Sublimation may be performed to remove most of the ammonium. In other words, the aluminum halide may be removed by sublimation. , sublimation so that the remaining ammonium halide is contained by the ionically conductive material. may be performed.
[0037] In another embodiment, the decomposition of the ammonium-containing complex metal halide is carried out by It helps remove reaction products other than the solid solution. For example, water, CO2, ammonia, A. Halogens can be evaporated.
[0038] Alternatively, the starting ammonium-containing complex metal halide may be formed in one step. The materials may be heated to higher temperatures. An exemplary one-step reaction is shown below: 3 * Li2CO3+ RE2O3+ 18 * NH4Br ----> 2 * (NH4)3Li3REBr9+ 6 * H2O+ 3 * CO2+ 12 * NH3.
[0039] In particular, heating is performed so that the decomposition of ammonium and the solid-state reaction can be carried out simultaneously. For example, the heating temperature can be adjusted to allow the formation of a solid solution and the sublimation of ammonium halide. To achieve this, the temperature can be in the range of 250°C to 650°C or up to 800°C. When using a one-step synthesis to form complex metal halides, relatively high content It has been noted that oxyhalides may be formed.
[0040] In another embodiment, the process 100 comprises: In one embodiment, the complex metal halide may comprise M 3- z Me k+ X 3-z+k In another embodiment, the complex metal halide may be represented by M 3-z (Me k+ ) f X 3-z+k*f where 0≦f≦1.
[0041] In some embodiments, cooling may be performed after decomposition. For example, cooling may be performed using air, dry air, or In another example, the cooling temperature may be at most 100°C, at most It may be 200°C or less, such as 70°C, at most 50°C, or at most 30°C. In an embodiment, the cooling may be carried out in a dry atmosphere at room temperature (e.g., 20 to 25°C). Optionally, Ar or N2 can be used to facilitate cooling.
[0042] In another aspect, the ionically conductive material comprising the complex metal halide is formed after cooling. Good too.
[0043] In embodiments, the complex metal halide has a specific content of residual ammonium halide. In at least one example, the ion-conducting material can be formed by including: At least 2 ppm of ammonium halide based on the total weight of the complex metal halides; For example, at least 10 ppm, at least 100 ppm, at least 300 ppm, At least 500 ppm, at least 0.2 wt%, at least 0.5 wt%, or less In another example, the ion-conducting The material may contain up to 5 wt. % of the complex metal halide by weight, e.g., up to 3 wt. % of the complex metal halide by weight. The complex metal halides may include ammonium halides. The residual ammonium halide content is within the range including either the minimum or maximum value specified. It will be appreciated that in at least one example, the complex metal halide may include: It may be essentially free of ammonium halide.
[0044] In an embodiment, the ionically conductive material is a powder comprising particles of a complex metal halide. In one embodiment, the powder has a particle size of at least 0.3 microns, An average of at least 0.1 microns, such as 0.5 microns, or at least 1 micron In another embodiment, the average particle size can be up to 1mm, max 800 microns, max 500 microns, max 200 microns, max 100 mm Kron, up to 50 microns, up to 10 microns, up to 5 microns, or up to 1 micron In certain embodiments, the powder may be any of the minimum or maximum values set forth herein. In another aspect, the powder may comprise particles having an average particle size ranging from 0.01 to 0.01 mm. , may contain agglomerated particles.
[0045] In a further aspect, the particles promote improved formation and performance of the electrolyte and / or electrode. The particles may have a particular shape that can be expanded. For example, the particles may be spherical or elongated. In another example, the particles may have the shape of rods, flakes, or needles. The particle shape can be used to determine the two-dimensional or It can be selected according to the one-dimensional anisotropy.
[0046] In another aspect, the powder is suitable for forming electrolytes and / or electrodes with improved ionic conductivity. The particles may have a particular average aspect ratio of length:width to promote In one example, the average aspect ratio is at least 1, for example at least 1.2, 1.5, at least 2, at least 2.3, at least 2.5, at least 2.8, or may be at least 3, and in another example, the average aspect ratio may be at most 30, at most 25, or at most 22, up to 20, up to 15, up to 12, up to 10, up to 8, up to 5, or up to 4 Furthermore, the particles may have any of the minimum and maximum values set forth herein. It may have an average aspect ratio within the range.
[0047] In embodiments, the ionically conductive material may contain relatively low amounts of certain impurities. The impurities are Me k+ X k Simple metal halides, including rare earth halides nitrides, alkali halides such as LiCl and / or NaCl, Mn, and Me x N y The coefficients x and and y are neutral Me x N y are the valences of N and Me relative to In some examples, impurities include amides (NH2), imides (NH), hydroxides (OH), ammonia, (NH3), or any combination thereof.
[0048] In an embodiment, the complex metal halide is M 3-z (Me k+ ) f X 3-z+k* f where -3≦z≦3; 2≦k<6; and 0≦f≦1. In certain embodiments, f is not zero. In particular embodiments, z<3. In this embodiment, when f=0, z may not be 3. M includes an alkali metal element. Me is a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element , hexavalent metallic elements, or any combination thereof; and X is halo. It may contain halogens.
[0049] In another embodiment, the complex metal halide is M 3-z Me k+ X 3-z+k Expressed as where -3≦z≦3; M can include an alkali metal element; M can be a divalent metal element, trivalent metal element, tetravalent metal element, pentavalent metal element, hexavalent metal element or any of them and X can include a halogen. In this case, z<3.
[0050] In one aspect, M is one or more alkali metals including Li, Na, Cs, and Rb. It can include a metal element. In a further embodiment, M can include Li. For example, M can include Li. In another embodiment, M can include Li and another arsenic. For example, M can be Li and any of Na, Cs, and Rb. In another example, M can include at least one of Li and Na, Cs, and In a more specific example, M can include at least one of Li and Rb. In another embodiment, M can be a combination of Na, or Na and Cs. In another example, M can be selected from the group consisting of Na and Rb. Cs.
[0051] In certain embodiments, Na accounts for up to 40 mol % of M, e.g., up to 34 mol % of M. For example, M can contain 0 mol% to 40 mol% Na. In particular examples, M is up to 20 mol % Na, more particularly up to 10 mol % In at least one example, Na can comprise 40 mol % to 10 mol % of M. It can comprise 00 mol %.
[0052] In further specific embodiments, Li is at least 50 mol % or less of M. At least 60 mol %, or at least 66 mol %, or at least 75 mol % In certain examples, M may contain 60 mol% to 100 mol% Li. can be done.
[0053] In another example, Cs is at least 25 mol % of M, e.g., at least 30 mol % of M. , at least 40 mol %, or at least 50 mol %, and other examples In the case of M, Cs is at most 50 mol%, or at most 40 mol%, or at most 30 mol%, or may account for up to 20 mol % or up to 10 mol %, and in certain instances, Cs may account for up to 20 mol % or up to 10 mol % of M It may account for up to 1 mol %.
[0054] In embodiments, the complex metal halide is (Li 1-d ,Nad ) 2Li 1-z M e k+ X 3+k-z 、 where 0 < d < 1; -0.95 ≤ z ≤ 0.95; Me includes divalent metal elements, trivalent metal elements, tetravalent metal elements, pentavalent metal elements, hexavalent metal elements or any combination thereof, and X can include halogen, and can be represented by valence metal elements, trivalent metal elements, tetravalent metal elements, pentavalent metal elements, hexavalent metal elements or any combination thereof, and X can include halogen, and can be represented by valence metal elements, trivalent metal elements, tetravalent metal elements, pentavalent metal elements, hexavalent metal elements or any combination thereof, and X can include halogen, and can be represented by
[0055] In an embodiment, the composite metal halide represented by (Li 1-d-e , Na d , M’ e ) 2Li 1-z’ (Me k+ ) f X 3+k*f-z satisfies 0 ≤ d ≤ 1; 0 ≤ e < 1; -3 ≤ z ’ ≤ 3; 2 ≤ k < 6; 0 ≤ f ≤ 1; M’ can include at least one of K, Rb and Cs. And Me can include divalent metal elements, trivalent metal elements, tetravalent metal elements, pentavalent metal elements, hexavalent metal elements, or any combination thereof; and valence metal elements, trivalent metal elements, tetravalent metal elements, pentavalent metal elements, hexavalent metal elements, or any combination thereof; and valence metal elements, trivalent metal elements, tetravalent metal elements, pentavalent metal elements, hexavalent metal elements, or any combination thereof; and X includes at least halogen. In a particular aspect, z’ < 3. In a particular aspect d + e > 0. In a particular aspect, f is not 0. In a more particular aspect, e = 0 and d is not zero.
[0056] In one aspect, d can be at least 0.01 or at least 0.05, or at least 0.1 or at least 0.2. In another aspect, d can be at most 0.8 or at most 0.5. In a particular aspect, d can be in a range including either the minimum value or the maximum value. In a particular aspect, d can be in a range including either the minimum value or the maximum value.
[0057] In one aspect, e can be at least 0.01 or at least 0.05, or at least In another embodiment, e is at most 0.8 or at least 0.1. In certain embodiments, e may be at most 0.5. The range can be inclusive of either
[0058] In an embodiment, Li 3-z Me k+ X 3-z+k Complex metal halides represented by is -0.95≦z=<0.95, and Me is a divalent metal element, a trivalent metal element, a 4 a valent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof and X may include a halogen.
[0059] In some embodiments, z is at most 0.5, e.g., at most 0.3 or at most 0.2. In another embodiment, z is at least −0.5 or at least −0.2. In certain instances, z may be any of the minimum and maximum values noted herein. When z is not 0, the complex metal halide is non-stoichiometric. When z is 0, the complex metal halide can be stoichiometric. do.
[0060] Exemplary divalent metallic elements are Mg and / or Ca, Zn, or any combination thereof. In certain embodiments, Me may include an alkaline earth element such as Z. In certain embodiments, the compound may comprise: Ions with relatively small radii, such as Zn and Mg, are halogen-containing or This may be particularly suitable for Cl-containing iridium compounds with relatively large radii, such as Ca. This may be particularly suitable when the halogen is or contains Br. In certain embodiments, including a substitution ion having a larger radius than the base ion includes: It may be useful for widening the ion conduction channels in electrolyte materials. For example, Me It may contain Ca and Y, and Ca may be suitable for partial substitution of Y. In another embodiment, divalent elements with relatively light weights, such as Mg, Zn, and Ca, are used. In certain embodiments, when Y is replaced by Sr or Ba, S Compounds of rX2 or BaX2 may be formed, which are complex metal halides. It can be an impurity that affects bulk ionic conductivity.
[0061] Exemplary trivalent metallic elements include rare earth elements, trivalent metals other than rare earth elements, such as In, Specific examples include Ga, Al, or Bi, or any combination thereof. Me can include Sc, Y, La, Gd, or any combination thereof. In more particular examples, Me can include Y, Gd, or a combination thereof.
[0062] Exemplary tetravalent metallic elements include Zr, Hf, Ti, Sn, Ge, Th, or any of the foregoing. In a particular example, Me can include Zr and Hf. In another particular example, Me can include Zr.
[0063] Exemplary pentavalent elements include Ta, Nb, W, Sb, or any combination thereof. This can be done.
[0064] In some embodiments, Me is selected from the group consisting of rare earth elements, alkaline earth elements, 3d transition metals, Zn , Zr, Hf, Ti, Sn, Th, Ge, Ta, Nb, Mo, W, Sb, In, Bi, S The material may include c, Yb, Al, Ga, Fe, or any combination thereof.
[0065] In further embodiments, Me includes a rare earth element, Zr, or any combination thereof. It can be done.
[0066] In another embodiment, Me is Y, Ce, Gd, Er, Zr, La, Yb, In, Mg, Zn , or any combination thereof.
[0067] When Me contains multiple metal elements, k is the average value of the total valence of each Me metal element. For example, if Me contains equal moles of trivalent and tetravalent elements, k = (3 + 4) / 2 = 3.5. In certain embodiments, k is 3 or 4 or 5 may be.
[0068] In further embodiments, Me is a rare earth element including Y, Gd, La, and / or Sc. Elements, alkaline earth metal elements, 3d transition metals, Zn, Zr, Hf, Ti, Sn, Th, Ta , Nb, Mo, W, Sb, In, Bi, Al, Ga, Ge or any combination thereof In a particular example, Me can include Y, Gd, Zr, or any combination thereof. In certain instances, Me may be partially substituted by another Me element. For example, Y may be included in the complex metal halide to improve the crystal structure. It can be replaced by a certain content of another Me element, which can promote the structure and properties. In a specific example, Me can be present in a mixture of up to 70 mol % Y and 5 mol % to 30 mol % of substitutional Me element. In a further example, Y may be a complex metal halide. Partly due to the Me element, which has a suitable effective ionic radius that can enable the formation of a stable phase of In a specific example, the element Me is substituted with an effective ionic radius of 103.2 A, which is smaller than that of La. small, with an ionic radius at least similar to the effective ionic radius of Li, 0.76A. In a more specific example, the effective ion current of the element Me is 0.76A±5% to 93.5A±5%. The radius of curvature may be 0.01.
[0069] In certain embodiments, Me is Gd, Y, Ce, Er, Zr, Yb, or any of the foregoing. For example, Me can consist of Y. In another example, Me comprises Y and at least one of Ce, Er, Zr, and Gd. In a further example, Me includes Yb and Ce. In another example, Me includes In. , Y, Zr, Hf, Sc, Zn, and Mg.
[0070] In some embodiments, X can include at least one of Cl, Br, I, and F. For example, X can include Cl or Br, and in another example, X can include F. In another example, X can include at least two of Cl, Br, and I. In yet another example, X can include all of Cl, Br, and I.
[0071] In some embodiments, X can include an element other than a halogen. In a similar manner, X may contain an anionic group in addition to a halogen. The groups are amide (-NH2), -(NH) 0.5 (imide), hydroxide (-OH), -BF 4, -BH4 (borohydride), or a combination thereof. may be included as an impurity or a dopant.
[0072] In certain aspects, X is selected from at least one of F, Cl, Br, and I, and any of Optionally, -NH2 (amide), -(NH) 0.5 (imide), -OH (hydroxide), -BH 4 (borohydride), -BF4 group, or an anion containing any combination thereof For example, X may contain one or both of Cl and Br and at least one of In a further example, X can include F and at least one anionic group. In at least one embodiment, X can be: It may be one or more halogens.
[0073] In a specific example, M is Li and Me is a combination of In, Mg, Zr, and Sc. and X can be Cl or a combination of Cl and an anionic group.
[0074] In another particular example, M is Li, Me is Y, Zr, and Hf, and X is Cl or or a combination of Cl and an anionic group.
[0075] In another specific example, M is Na, Me is Zr, and X is Cl or Cl and anion. It is possible for the alkyl group to be a combination of alkyl groups.
[0076] In certain embodiments, the complex metal halide is (Li (1-d-e) ,Na (d ) ,M' (e) )2Li (1-z) Me 3+(1-u-p-q-r) Me 4+ (u) Me 2+ (p) Me 5+ (q) Me 6+ (r)(Cl(1-y-w) Br (y) I (w))( 6+u-p+2q+3r-z) where 0≦d≦1, 0≦e<1;-3≦z≦3; M' contains at least one of K, Rb, and Cs; 3+ are rare earth elements, In, Bi, Sc, Y, Al, Ga or any combination thereof; Me 4+ is Zr 4+ ,Hf 4+ ,Ti 4+ ,Sn 4+ ,Th 4+ ,Ge 4+ or any combination thereof That's it. 2+ is Mg 2+ ,Zn 2+ ,Ca 2+ ,Yb 2+ ,EU 2+ or it any combination of these; 5+ Ta 5+ ,Nb 5+ ,W 5+ ,Sb 5+ Ma or any combination thereof; 6+ is W 6+ ,Mo 6+ or those Any combination: 0<=w<=1; 0<=y<=1; -0.95 <z<0.9 5; 0<=u<0.95; 0<=p<0.95; 0<=q<0.95; and 0<=r< It is 0.95.
[0077] In certain situations, M 3+ is Y 3+ , Gd 3+, In 3+ , Er 3+ ,Sc. 3+ , or any combination thereof. In a more particular aspect, M 3+ is Y 3 + , Gd 3+ , In 3+ , Er 3+ ,Sc. 3+ or any combination thereof. It can be achieved.
[0078] In certain situations, M 4+ is Zr 4+ , Hf 4+ , Ce 4+ , or a combination thereof In a more particular aspect, M 4+ is Zr 4+ ,Hf 4+ ,Ce 4+ , or a combination thereof.
[0079] In another specific aspect, any one or more of p, q, r, and u can be 0. In a more particular aspect, p, q, r, and u can all be 0.
[0080] In certain embodiments, k can be 2 or 3 or 4 or 5.
[0081] In another particular embodiment, the complex metal halide is (Li (1-d), Na (d) ) 2Li (1-z) RE (1-u) Zr 4+ (u) (Cl (1-y) Br (y))(6+u -z ), where 0 <d<1;0<z<0.95;および0<=u<0.95であ It is. In one example, d is at least 0.0001, at least 0.001, at least 0. 005, at least 0.008, at least 0.01, at least 0.02, at least 0.03, at least 0.05, or at least 0.06. In a further example d can be at most 0.5, at most 0.3, at most 0.2, at most 0.1, at most 0.08, at most 0. 06, at most 0.05, at most 0.04, or at most 0.03. In a further example , d can be within a range that includes any of the minimum and maximum values pointed out in this specification. For example, 0 < d < 0.05. In a further example, z is at least 0.02, at least 0.03, at least 0.05, at least 0.07, at least 0.09, at least 0.1, at least 0.15, at least 0.18, or at least 0.2 can be. In another example, z can be at most 0.5, at most 0.4, at most 0.38, at most 0.3 5, at most 0.33, at most 0.3, at most 0.28, at most 0.25, at most 0.23, or at most 0.2. Further, z can be within a range that includes any of the minimum and maximum values pointed out in this specification. For example, 0 < z < 0.2. In another example, u is at least 0.01, at least 0.03, at least 0.05, at least 0.07, at least 0.09, at least 0.1, at least 0.13, at least 0.15, at least 0.18, at least 0.2, at least 0.22, at least 0.25 or at least 0.3 can be. In another example, u can be at most 0.8, at most 0.78, at most 0 .75, at most 0.73, at most 0.7, at most 0.68, at most 0.65, at most 0.63, or at most 0.6. Further, u is the minimum and maximum values pointed out in this specification It can be in an inclusive range, for example, 0.2 <u<0.6である。
[0082] In certain embodiments, the complex metal halide may be doped with a dopant. In certain instances, Li may be partially substituted by a dopant. The dopant can include ammonium, for example, ammonium halide NH4X. where X can be Cl, Br, I, F, or any combination thereof.
[0083] In one embodiment, the complex metal halide contains more than 100% by weight of the complex metal halide. At most 20wt%, for example at most 15wt%, at most 10wt%, at most 8wt%, May contain at most 5 wt. % or at most 3 wt. % ammonium halide In another embodiment, the ammonium halide is ammonium halide based on the total weight of the complex metal halide. at least 10 ppm by mass of ammonium halide, e.g., at least 100 ppm; At least 500 ppm, at least 0.1 wt%, at least 0.3 wt%, at least ions at a content of at least 0.5 wt%, at least 0.8 wt%, or at least 1 wt% In addition, complex metal halides may be present in the conductive material at least as large as the minimum values set forth herein. and a maximum content of ammonium halide in the range including either do.
[0084] Referring to FIG. 2, an exemplary process 200 for forming a solid, ionically conductive material is The process 200 is illustrated in blocks 102, 104, and 106 of FIG. and includes steps similar to those described in the embodiment with respect to process 100. can be done.
[0085] After obtaining the complex metal halide in block 106, the process 200 continues with block 208. In an embodiment, the process 200 can continue with the step of forming a complex metal halide. In one embodiment, the solid ionically conductive material may include a single crystal material comprising: In this method, crystal growth is performed in a crucible made of a material inert to complex metal halides. For example, the crucible may be made of quartz, alumina, silica-alumina, BN, It may be made of glassy carbon or graphite. The lite may have a coating of pyrolytic carbon.
[0086] The complex metal halide obtained by the process 100 can be electrochemically reacted to form a single crystal. In one embodiment, the process 200 can be used to fabricate complex metal hardware. In some embodiments, the method may include partially or completely melting the halogenide. In this case, a dopant material such as a metal compound is added to the melt to form a complex metal halide. The substitution of more than one metal element can be promoted.
[0087] In a further embodiment, the process 200 comprises single crystal blocks up to 10 centimeters in size. A specific crystal growth rate can be achieved that can promote the growth of single crystals with macroscopic sizes such as For example, the growth rate may be at least 0.2 mm / hour, at least 0. In another example, the growth rate may be 3 mm / hour, or at least 0.5 mm / hour. The speed can be up to 10mm / hour, e.g. up to 8mm / hour, up to 6mm / hour, up to 5mm / hour, up to 3 mm / hour, or up to 1 mm / hour. The growth rate is within a range including any of the minimum and maximum values set forth herein. can be done.
[0088] In another embodiment, the process 200 can include cooling the melt. In an embodiment, the cooling is controlled to support the formation of single crystals having complex metal halides. In certain embodiments, cooling can be carried out in a controlled manner. This can be accelerated by an external thermal field with a cooling rate of 0 °C / hr. The starting materials for complex metal halides are often impurities such as simple metal halides. In these instances, the melt may form incommensurate melt phases, and the melt may undergo self-fluxing conditions. In order to promote the formation of stoichiometric single-phase crystals at room temperature, an excess of complex metal halides and dopant was added. It is possible for the material to contain off-stoichiometric mixtures containing the cation exchange material.
[0089] The single crystal is formed by the process 100 and is a composite alloy as described in the embodiments herein. The metal halide may have the same composition as the metal halide.
[0090] Single crystals can be small chunks of the order of a few millimeters, or dense blocks or large chunks of several tens of centimeters in size. Ingots are also acceptable.
[0091] In an embodiment, the ingot or block is free of visible impurities and / or parasitic phases. If present, they may be polished to remove them.
[0092] In a further embodiment, the single crystals are ground to form a fine powder having single crystal particles. In an exemplary application, the single crystal particles may be used for ion generation in electrochemical devices. In another embodiment, single crystal The ingot or block may be sliced into thin sheets. For example, a thin sheet may be 5 mm thick. The thickness of the clon can be up to 500 microns.
[0093] In certain embodiments, the process 200 forms a single crystal having a particular crystallographic orientation. In one embodiment, oriented growth of a single crystal can be performed. In certain embodiments, oriented crystal growth can be performed on crystals that are anisotropic. In one embodiment, the pellets or particles are elongated in the crystallographic direction with higher electrical conductivity. In another example, to promote oriented growth of single crystals, A high temperature gradient such as °C / cm or higher can be applied. Alternatively, the permeability or dielectric constant can be determined. For crystals with anisotropy in the refractive index, solidification under a strong permanent magnetic field, a strong electric field, or Oriented crystal growth can be achieved using any combination of the following: The method utilizes a supporting seed layer with a lattice constant close to that of the oriented ceramic material, and Solidification in vivo may allow the oriented polycrystalline structure to be maintained.
[0094] In another embodiment, the crystallographic direction having the higher electrical conductivity is through the thickness of the thin sheet. The single crystal can be sliced as follows:
[0095] In certain embodiments, the ionically conductive material is <hkl>or <hklm>It is expressed as and may include oriented crystalline materials such as single crystal materials having a crystallographic orientation <hkl>or <HK The ionic conductivity in the crystallographic orientation of LM> is related to the different crystallographic orientations to which the single crystal can be oriented. The ionic conductivity is higher than that at
[0096] For example, Li3YBr6 is <001> Compared with the crystallographic orientation <100> In High ionic conductivity. Crystallographic orientation <100> The Li3YBr6 single crystal has It may be formed to have a higher bulk ionic conductivity. A slice of Li3YBr6 having a cut surface extending along the 01> axis is formed from the single crystal and its thickness is Crystal orientation <100> It may be extended to.
[0097] Referring to Figure 3A, there is shown a sheet 300. In an embodiment, the sheet 300 is , may comprise a single crystal as described in the embodiments herein. 3B shows a crystallographic view of a single crystal. A single crystal has layers whose lengths are aligned in the crystallographic directions. <100> Extends to layers The stack of crystallographic directions <001> It may have a mica-like layer structure that extends to the Crystals are crystallographically oriented <100> In <001> Larger ionic conductance compared to In a particular example, the thickness t of the sheet 300 can have a crystallographic orientation <10 In a further example, one of the major surfaces of 302 and 304 or Both can be sliced surfaces. Alternatively, the sheet 300 can be a crystallographic It can be formed by oriented crystal growth to have a crystallographic orientation, where the thickness t is <100> Extends to.
[0098] The formation process of embodiments herein allows for the formation of ionically conductive materials with higher purity. It is noted that ionically conductive materials with higher purity can be used for further It is further noted that the ionic conductivity of the cellulose acylate polymer may be improved.
[0099] Complex metal halides using conventional methods such as solid-state reactions using ball milling The formation of HCl can result in high impurity contents such as simple metal halides. Use complex metal halides with a high content of simple metal halides, or use simple compounds directly. Starting materials include Bridgman-Stockberger, Gradient-Freeze, and Chalk. When crystals are grown according to the Larski, Bagdasarov (horizontal Bridgman) process, The melt exhibited incongruent melting, resulting in the formation of high contents of impurity and parasitic phases in the resulting crystals. The impurity and parasitic phases are LiX and Me k+ X k One or more of These include simple metal halides, where X is a halogen such as Cl and / or Br.
[0100] The process of the present embodiment forms complex metal halides with low impurity content. In an embodiment, the complex metal halide may be a complex metal halide. A total content of simple metal halides of at most 15 wt.% based on the total weight of halides, e.g. At most 12wt%, at most 11wt%, at most 10wt%, at most 9wt%, At most 8wt%, at most 7wt%, at most 6wt%, at most 5wt%, at most 4wt%, at most 3wt%, at most 2wt%, at most 1wt% or at most 0. In certain embodiments, the complex metal halide may comprise 5 wt % or more. The single crystal of can be essentially free of simple metal halides. For example, all The total content of simple metal halides was less than 0.2 wt% based on the weight of the single crystal. The complex metal halides of the embodiments herein may also be prepared using conventional methods. It is noted that the SiO2 nanoparticles have a higher bulk ionic conductivity compared to the previously reported SiO2 nanoparticles.
[0101] In embodiments, crystal growth can be performed to facilitate further purification of the complex metal halide. In a further embodiment, the crystal growth can be performed to improve bulk ion conduction. This can promote the formation of an ionically conductive material having electrical conductivity. The single crystal of the composite metal halide has the same composite metal halide of the embodiments herein. It has further improved bulk ionic conductivity compared to non-single crystalline forms (e.g., powders) in which it is used. It is noteworthy that there is a tendency to
[0102] In at least one embodiment, the single crystals of the embodiments herein contain an insufficient amount of nitride-based phases. The nitride phase may contain a low content of metal nitrides, metal oxynitrides, metal carbonitrides, etc. The alloy may comprise one or more phases of nitrides, nitrides, or any combination thereof. The formation of oxide-based phases can result from process 100, process 200, or a combination thereof. In some embodiments, the presence of certain species of metal nitrides, such as Li3N, may help to improve the bulk ionic conductivity of the metal halide material.
[0103] Referring to FIG. 4, a process 400 for forming an ionically conductive material is illustrated. Process 400 is illustrated in FIG. 1 and described in the embodiment with respect to process 100. All steps may be included.
[0104] In an embodiment, the process 400 forms a solid conductive material comprising an oriented ceramic material. In one embodiment, the composite alloy formed by process 100 Metal halide grains can be used. In one example, the grains have a characteristic shape, such as an elongated shape. The particles can have a certain shape, with the longitudinal axis of the particles being aligned with the crystalline structure having a higher ionic conductivity. In another example, the particles may be arranged to extend parallel to the direction of the optical orientation. Casting, compressing, pressing, heating, molding, or any combination thereof to obtain In another example, a magnetic field, an electrical discharge, a thermal gradient, or a combination thereof may be used. This may promote the crystal orientation of the ceramic particles.
[0105] In another embodiment, the process 400 includes crystal growth to form an oriented ceramic. In one embodiment, process 400 can be similar to process 200. In a further aspect, the crystal growth can include forming a melt of a particular For example, the growth rate may be at least 8 mm / hour, at least 10mm / hour, at least 15mm / hour, or at least 20mm / hour In another example, the growth rate may be up to 80 mm / hr, up to 70 mm / hr, or up to It can be up to 60 mm / hour, up to 50 mm / hour, or up to 40 mm / hour. In this case, the growth rate is within a range including any of the minimum and maximum values stated herein. In another aspect, a thermal gradient can be used to promote oriented polycrystalline crystal growth. can be applied.
[0106] In an embodiment, the process 400 may be implemented as described in the embodiment relating to the process 200. In one embodiment, the single crystal pellets are formed by The crystallographic orientation of the ceramic ionically conductive material may be determined by the crystallographic orientation of the ceramic ionically conductive material. In one example, molding, compressing, pressing, heating, forming, or any combination thereof may be used. may be used to promote the formation of crystal-oriented ceramic ion-conducting materials. In certain instances, the single crystal pellets may be oriented and have a preferred crystallographic orientation. Cut.
[0107] In one example, the complex metal halide has a crystallographic orientation <100> Higher ions in Conductivity and crystallographic orientation <001> Anisotropic with lower ionic conductivity Referring to FIG. 3b, a single crystal or ceramic plate of a complex metal halide 322 is The letts can be arranged as shown to form a crystallographically oriented ceramic material.
[0108] The solid, ionically conductive materials of embodiments herein can be in different forms. In embodiments, the ionically conductive material may include a powder containing a complex metal halide. In another embodiment, the ionically conductive material may comprise a single crystal of a complex metal halide. For example, the ionically conductive material may include a powder containing single crystal particles. In the example, the ion-conducting material may be a single crystal sheet, a single crystal film, a single crystal block, a single crystal, or a single crystal. The material may include a single crystal ingot, or another form of single crystal, or any combination thereof. In a further embodiment, the ionically conductive material is a composite metal halide. For example, the ceramic material may include ceramic particles, single crystals, particles, or any combination thereof.
[0109] In another embodiment, the solid, ionically conductive material is polycrystalline, single crystalline, or crystallographically oriented. For example, the solid conductive material may be a complex metal halide. In another example, the solid conductive material may be a single crystal of a complex metal halide. In another example, the solid conductive material may be a composite metal halo. The material may be a crystallographically oriented crystalline material of a fluoride.
[0110] In embodiments, the solid, ionically conductive material may include a content of impurities. may exist as a separate phase from the complex metal halide or may exist in the same phase as the metal halide. For example, simple metal halides are not complex with complex metal halides. It may exist in different phases. For example, ammonium halide may be combined with complex metal halides. In particular, the solid ionically conductive material may be of the same general type as may be represented by the formula, but may be formed using a process different from that indicated in the embodiments herein. The solid ionically conductive material may have improved purity compared to conventional solid ionically conductive materials, e.g. The total content of all impurities (also referred to as "total content of impurities") is Up to 15 wt% based on the weight of the complex metal halide in the solid ionically conductive material of the embodiment For example, the total content of impurities may be It may be at most 14 wt%, for example at most 13 wt%, at most 12 wt%, at most At most 11wt%, at most 10wt%, at most 9wt%, at most 8wt%, at most 7wt%, at most 6wt%, at most 5wt%, at most 4wt%, at most 3wt% , at most 2 wt%, at most 1 wt%, at most 0.5 wt%, at most 0.3 wt% , at most 0.1 wt%, at most 500 ppm, at most 300 ppm, at most 10 0 ppm, at most 50 ppm, at most 40 ppm, at most 30 ppm, at most 2 It is possible to obtain complex metal halides with a weight concentration of 0 ppm or at most 10 ppm. In the example, the complex metal halide is at least 0.05 wt. 0.2 ppm, e.g., at least 0.5 ppm by weight of complex metal halides, It may contain a total impurity content of at least 1 ppm, or at least 2 ppm. In another embodiment, the total content of impurities is within any of the minimum or maximum values set forth herein. The range may include either one of them.
[0111] The content of impurity phases can be determined as follows: Each impurity phase is added to the parasitic phase. Rietveld refinement for quantitative analysis through the presence of corresponding characteristic diffraction peaks The Rietveld method (RR) can be detected by XRD analysis coupled with XR Analyze the shape and position of the peak in the D diagram, and gradually increase the angle by X. Two sets of data are collected during RD diffraction and converted into the ratio of different phases to quantitatively determine the contribution of each phase. can be identified.
[0112] Regarding nitride impurity phases, in particular, the nitride impurity phase is 0.1% in molar or mass amount. If present at less than 1000kJ / kg, LECO analysis can be used to determine and quantify its presence. LECO analysis is performed by combusting a sample and measuring the thermal conductivity or infrared absorption of the boiling raw gas. It is based on the analysis of the presence of nitrogen (or sulfur, carbon, hydrogen, or oxygen) in the water.
[0113] In a further aspect, the metal nitrides, metal oxynitrides, and The content of all nitride-based impurity phases, such as metal-carbon nitrides and / or metal-carbon nitrides, is At most 0.3 wt%, at most 0.2 wt%, at most 0 .1wt%, at most 500ppm, at most 300ppm, at most 100ppm, at most 50 ppm, at most 40 ppm, at most 30 ppm, at most 20 ppm, or or at most 10 ppm by weight of complex metal halides. The total metal nitride content is at least 0.2 ppm by weight of the complex metal halide. , for example, at least 0.5 ppm, at least 1 ppm by weight of the complex metal halide ppm, or at least 2 ppm. In another embodiment, all nitride-based The content of the phase may be in a range including either the minimum or maximum value stated herein. stomach.
[0114] In a further embodiment, the alkali halide (MX) content is a complex metal halide At most 10 wt% of the weight of the object, for example, at most 9 wt%, at most 8 wt%, At most 7wt%, at most 6wt%, at most 5wt%, at most 4wt%, at most 3 wt%, at most 2wt%, at most 1wt%, at most 0.5wt%, at most 0.3 wt%, at most 0.2wt%, at most 0.1wt%, at most 500ppm, at most At most 300 ppm, at most 100 ppm, at most 50 ppm, at most 40 ppm, Not more than 30 ppm, not more than 20 ppm, or not more than 10 ppm of complex metal halides In another example, the content of MX is based on the weight of the complex metal halide. at least 0.2 ppm relative to the weight of the complex metal halide, e.g., at least It can be at least 0.5 ppm, at least 1 ppm, or at least 2 ppm. In another embodiment, the MX content includes any of the minimum or maximum values set forth herein. It may be within a range including.
[0115] In a further embodiment, a metal oxyhalide (MeOX), such as a rare earth oxyhalide The content of is at most 5 wt% relative to the weight of the complex metal halide, for example at most 4 wt%, at most 3wt%, at most 2wt%, at most 1wt%, at most 0.5wt %, at most 0.3wt%, at most 0.2wt%, at most 0.1wt%, at most 5 00ppm, at most 300ppm, at most 100ppm, at most 50ppm, at most at most 40 ppm, at most 30 ppm, at most 20 ppm, or at most 10 ppm In another example, MeO The content of X phase is at least 0.2 ppm by weight of the complex metal halide, e.g. , at least 0.5 ppm by weight of complex metal halide, at least 1 ppm; In another embodiment, the content of the MeOX phase is: It may be within a range that includes any of the minimum or maximum values stated herein. In embodiments, the complex metal halide can be essentially free of MeOX.
[0116] In a further embodiment, the metal nitride Me x N k The content of the compound metal halide is At most 0.3 wt% of the amount, for example at most 0.1 wt%, at most 500 ppm , at most 300 ppm, at most 100 ppm, at most 50 ppm, at most 40 ppm pm, at most 30 ppm, at most 20 ppm, or at most 10 ppm In another example, the content of the metal nitride may be small relative to the weight of the complex metal halide. At least 0.2 ppm, e.g., at least 0.5 ppm by weight of the complex metal halide ppm, at least 1 ppm, or at least 2 ppm. So, metal nitride Me x N k The total content of The range may include either of the above.
[0117] In a further embodiment, the metal nitride M x The N content is based on the weight of the complex metal halide. For example, maximum 0.1wt%, maximum 500ppm, maximum 300ppm m, max 100ppm, max 50ppm, max 40ppm, max 30ppm, max 20p In another example, the metal nitride content can be: At least 0.2 ppm by weight of the complex metal halide, e.g., At least 0.5 ppm, at least 1 ppm, or at least In another embodiment, the total content of metal nitrides MeN can be 2 ppm or less. The range may include either the minimum or maximum value stated.
[0118] In this disclosure, the total content of nitride-based phases and the alkali nitrides and Me x N k Metal nitrides such as The content can be detected by the following method. The ion-conductive material is a metal halide complex. Since halogen compounds are hygroscopic, they can be dissolved in water before use. Since there is no trace of chlorine, the aqueous solution can be filtered and then recovered for analysis. If present, it can be detected by X-ray diffraction analysis. If it is less than 0.2 wt%, LECO is used. You can.
[0119] Regarding the content of metal halides, X is the same as that of ionic conductive materials without dissolving them. It is possible to analyze it by X-ray diffraction.
[0120] In certain examples, the solid ionically conductive material is NH3, NH4X, or a combination thereof. In some embodiments, X may include NH3 and / or NH4 X may exist as a separate phase in addition to the complex metal halide. H3 and / or NH4X were dopants or impurities in complex metal halides. That's fine.
[0121] In yet another example, the solid ionically conductive material may be Li4(NH2)3Cl, Li7(NH 2) 6Cl, Li2Br(NH2), Li 13 [NH]6Cl, LiCl-NH3, Li Br-4NH3, or combinations thereof. In addition to the nitride, one or more compounds may be present in a separate phase. The compound may be a by-product resulting from processes 100, 200, and / or 300. In another example, the compound may be a dopant or impurity present in a complex metal halide. It's okay to have it.
[0122] In an embodiment, the ionically conductive material is a pelletized sample sandwiched between ion-blocking electrodes. at least 0.0 as measured by electrochemical impedance spectroscopy performed on the material 1 mS / cm, e.g., at least 0.05 mS / cm, at least 0.08 mS / cm , or at least 0.1 mS / cm, or at least 0.3 mS / cm, or at least It is possible for the bulk ionic conductivity to be 0.5 mS / cm. The ionic conductivity is at least 0.6 mS / cm, at least 1.2 mS / cm, or In another example, the ion exchange rate may be at least 1.8 mS / cm, or at least 2.2 mS / cm. Lux ionic conductivity: Max 15mS / cm, Max 13mS / cm, Max 11mS / cm, It can be up to 8mS / cm, up to 7.2mS / cm, or up to 6.2mS / cm. In certain instances, the bulk ionic conductivity may be greater than or equal to the minimum and maximum values noted herein. The bulk ionic conductivity can be in a range including any of the following at room temperature, such as 22°C: It can be measured at activation energies in the range of 0.2 eV and 0.5 eV. In this study, activation energies of 0 to 1 eV were used for temperatures from 200°C to -80°C. For temperatures between 80°C and -30°C, the activation energy is between 0.1 and 0.6 eV. When the temperature is above 0°C or below 10°C, the activation energy is 0.1 to 0 It can be 0.5eV.
[0123] In embodiments, the solid electrolyte may include an ionically conductive material. The material can be single crystalline, polycrystalline, or a combination thereof. Compared to previously developed complex lithium-based metal halide-containing solid electrolytes, In a particular example, the solid electrolyte may be an ion-conducting material. In a more specific example, the solid electrolyte may be composed of a single-crystal complex metal halide, Polycrystalline complex metal halides, or single crystals or oriented ceramics with specific crystal orientations In certain applications, the metal halide may be composed of oriented crystals containing complex metal halides. The electrolyte may comprise a crystallographically oriented solid ionically conductive material, It may have a thickness extending in a direction parallel to the orientation of the on-conductive material.
[0124] In embodiments, the composite ion-conducting layer may comprise an ion-conducting material and an organic material. The organic material may be included as a binder material, a polymer electrolyte material, or a combination thereof. In another example, the composite ion-conducting layer may be formed by adding a plasticizer, a solvent, or a combination thereof. An exemplary organic material may include polytetrafluoroethylene (PTF) E), polyvinylidene fluoride (PVdF), fluororubber, polypropylene, ethylene-propylene Propylene-diene monomer (EPDM), sulfonated EPDM, natural butyl rubber (NBR ), paraffin wax, polypropylene carbonate, polyisobutylene, polyvinylpyrrolidone may include ethylenediamine, polymethyl methacrylate, poly(propylene oxide), polyvinyl chloride, etc. Poly(vinylidene fluoride), poly(acrylonitrile), poly(dimethylsiloxane) ), poly[bis(methoxyethoxy)-phosphazene], polyethylene carbonate, poly Propylene glycol, polycaprolactone, poly(trimethylene carbonate), water Chlorinated nitrile butadiene rubber, poly(ethylene vinyl acetate), high density polyethylene, low density In another example, the material may be polyethylene, polyurethane, or any combination thereof. The composite ion conducting layer can include a lithium salt. Exemplary lithium salts include LiSbF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, LiAsF6, LiC LiO4, LiPF6, LiBF4, LiCF3SO3, or any combination thereof. do.
[0125] In another embodiment, the mixed electronic and ionic conducting layer may comprise an ionically conducting material. In one embodiment, the mixed electronic and ionic conductive layer may further comprise a positive electrode active material. Examples of positive electrode active materials include lithium ions such as Li(NiCoAl)O2 and LiCoO2. Sum-containing transition metal oxides, transition metal fluorides, polyanions, and fluorinated polyanions Materials, and transition metal sulfides, transition metal oxyfluorides, transition metal oxysulfides, transition metal oxynitrides, or any combination thereof, This is not limited to these.
[0126] In another embodiment, the mixed ionic and electronic conducting layer can include a negative electrode active material. Suitable negative electrode active materials include carbon materials such as artificial graphite, graphite carbon fiber, resin-burned carbon, and pyrolysis carbon. Phase-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol Resin-sintered carbon, polyacene. Pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, non-graphite Metallic materials such as lithium metal and lithium alloys, oxides, nitrides, tin compounds, ketones, etc. Ion compounds, or combinations thereof.
[0127] In some embodiments, the mixed ionic and electronic conductive layer comprises an electronically conductive additive. Examples of electronically conductive additives include carbon fiber, carbon powder, stainless steel fiber, and nickel. Nickel-coated graphite, etc., or any combination thereof.
[0128] In embodiments, the solid state lithium battery includes an electrolyte disposed between an anode and a cathode. Referring to Figure 5, a portion of an exemplary solid-state battery 500 is shown in cross section. The electrolyte layer 502 may be any of the electrolyte layers or composite layers mentioned in the embodiments herein. The anode 504 covers the electrolyte 502. In an embodiment, the negative electrode 504 The negative electrode may include a solid, ionically conductive material and a negative electrode active material. The electrode 504 may be a three-dimensionally structured negative electrode. In another embodiment, the negative electrode 504 The cathode 506 may be a metal anode. For example, the anode may be composed of lithium. The positive electrode 506 may be located on the opposite side of the electrolyte 506 from the positive electrode 502. In certain embodiments, the positive electrode 506 may include a positive electrode active material. , or a three-dimensionally structured positive electrode.
[0129] In a particular example, the electrolyte 502 can be a single crystal sheet 302 as illustrated in FIG. The anode 504 can be on the major surface 304 shown in FIG. The major surface 306 shown can be on a cathode 506 .
[0130] Using solid electrolyte materials, electrolytes, composite ion-conducting layers, negative electrodes, positive electrodes, or solid lithium Known techniques can be used to form the other components of the battery. Techniques include casting, molding, depositing, printing, pressing, heating, etc., or any combination thereof. In certain embodiments, the multi-layer structure may be formed by To achieve this, layers such as the electrolyte and the negative and / or positive electrodes are formed separately and then stacked to form multiple layers. Alternatively, a layer structure may be formed of the green electrolyte and the anode and / or cathode layers. A stack is formed, which is then pressed, heated, dried, or any combination thereof. Any further processing may be performed to form the final multi-layer structure.
[0131] In certain embodiments, the single crystal block or ingot is combined with the positive or negative electrode active material. Both can be processed, for example, by mechanical pressing or heat-activated co-extrusion, and can be used to form electrodes and Intimate electrolyte contact can be ensured.
[0132] In another particular embodiment, the single crystal blocks and ingots are used for the anode and / or cathode active materials. The electrons can be grown directly around the particles to form a mixed layer that is both electronically and ionically conductive. In one embodiment, the mixed ionic and electronic conductive layer comprises an inclusion containing the negative or positive electrode active material. In another embodiment, a mixed ionic and electronic conducting material may be used. The conductive layer is made of anode or cathode active material densely packed in a single crystal ingot or block. may include:
[0133] Many different aspects and embodiments are possible. Some of these aspects and embodiments are After reading this specification, those skilled in the art will be able to understand these aspects and implementations. It will be understood that the embodiments are illustrative only and do not limit the scope of the present invention. The configuration may be according to any one or more of the embodiments listed below.
[0134] Embodiment Embodiment 1. A solid ionically conductive material comprising a complex metal halide: The complex metal halide is doped with a dopant comprising ammonium; and Complex metal halides are M 3-z (Me k+ ) f X 3-z+k*f where , -3 ≤ z < 3; 2 ≤ k < 6; 0 ≤ f ≤ 1; M includes an alkali metal element. Me is a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, metallic elements, or any combination thereof; and X includes a halogen. Embodiment 2. A solid, ionically conductive material comprising: M 3-z (Me k+ ) f X 3-z+k*f A complex metal halide represented by -3 ≤ z < 3; 2 ≤ k < 6; 0 ≤ f ≤ 1; M includes an alkali metal element. Me is a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, and X comprises a halogen; Charge-neutral Me x N k or M x N, x is the valence of N, and k is M The valence of e. Embodiment 3. The solid, ionically conductive material of embodiment 1 or 2, wherein the composite alloy Group halides are (Li 1-d-e ,Na d ,M' e )2Li 1-z’ (Me k+ ) f X 3+k*f-z 1. A solid ionically conductive material characterized in that it is represented by: 0 ≤ d ≤ 1; 0≦e<1; M consists of at least one of Li, Na, and M'; and M' consists of at least one of K, Rb, and Cs. Embodiment 4.Li 1-d-e ,Na d ,M' e )2Li 1-z (Me k+ ) f X 3+k *f-z A solid ionically conductive material comprising a complex metal halide represented by -3 ≤ z < 3; 2 ≤ k < 6; 0 ≤ f ≤ 1; 0 <d≦1; 0≦e<1; M includes an alkali metal element. Me is a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, and X comprises a halogen; Charge-neutral Me x N k or M x N, x is the valence of N, and k is M The valence of e. M consists of at least one of Li, Na, and M', and M' consists of at least one of K, Rb, and Cs. It consists of at least one. Embodiment 5. z is -0.95 to 0.95, and M consists of Na and Li. 5. The solid ion-conductive material according to any one of aspects 1 to 4. Embodiment 6.Me is a rare earth element, an alkaline earth metal element, a 3d transition metal, Zn, Zr , Hf, Ti, Sn, Th, Ge, Ta, Nb, Mo, W, Sb, In, Bi, Al, G a, Fe, or a combination thereof. 10. The solid, ionically conductive material according to any one of claims 1 to 9. Embodiment 7. Me comprises a rare earth element, Zr, or any combination thereof; 7. The solid, ionically conductive material of any one of embodiments 1 to 6. Embodiment 8. Me is Y, Ce, Gd, Er, Zr, La, Yb, In, Mg, Zn, or any combination thereof. Ionically conductive materials. Embodiment 9. X is selected from the group consisting of at least one of F, Cl, Br, and I, and optionally, —NH 2 (amide), -(NH) 0.5 (imide), -OH (hydroxide), -BH4 (borohydride) anionic groups containing -Br, ... The solid, ionically conductive material according to any one of the first to eighth embodiments. Embodiment 10. The method of any one of embodiments 1 to 9, wherein Me comprises Gd, Y, or a combination thereof. 10. The solid ionically conductive material according to any one of claims 1 to 9.
[0135] Embodiment 11. The method of any one of embodiments 1 to 10, wherein Me comprises Ce, Y, or a combination thereof. 10. The solid, ionically conductive material according to any one of claims 9 to 19. Embodiment 12. The compound of any one of embodiments 1 to 9, wherein Me comprises Er, Y, or a combination thereof. 10. The solid ionically conductive material according to any one of claims 1 to 9. Embodiment 13. The compound of any one of embodiments 1 to 10, wherein Me is Yb, Ce, or a combination thereof. 10. The solid, ionically conductive material according to any one of claims 9 to 19. Embodiment 14. The method of any one of embodiments 1 to 9, wherein Me comprises Y, Zr, or a combination thereof. 10. The solid ionically conductive material according to any one of claims 1 to 9. Embodiment 15. Me is selected from two or more of In, Y, Zr, Hf, Sc, Zn, and Mg. 10. The solid, ionically conductive material of any one of embodiments 1 to 9, consisting of Embodiment 16. Any of embodiments 1 to 15, wherein the halogen is Cl, Br, I, or F. 10. The solid ionically conductive material according to any one of claims 1 to 9. Embodiment 17. The halogens consist of at least two of Cl, Br, I, and F. The solid, ionically conductive material according to any one of embodiments 1 to 16. Embodiment 18. Any one of embodiments 1 to 17, wherein the halogens consist of Cl, Br, and I. 2. The solid ionically conductive material according to claim 1 . Embodiment 19. The complex metal halide is represented by Li3-zMek+X3-z+k wherein Me is a rare earth element, Zr, or any combination thereof. and the solid, ionically conductive material of any one of 4 to 18. Embodiment 20. The solid, ionically conductive material of any one of embodiments 1 to 18. (Li 1-d Na d )2Li 1-z Me k+ X 3+k-z Composite metal halide represented by wherein Me comprises a rare earth element, Zr, or a combination thereof, and 0≦ d<1,-0.95≦z=<0.95.
[0136] Embodiment 21. The solid, ionically conductive material according to any one of embodiments 1 to 20. That is, z≦0.5 or z≦0.3 or z≦0.2. Embodiment 22. The solid, ionically conductive material according to any one of embodiments 2 to 21. wherein d≧0.01 or d≧0.05 or d≧0.1. . Embodiment 23: The solid ion-conductive material according to any one of embodiments 2 to 22. and d≦0. Embodiment 24: The solid ionically conductive material according to any one of embodiments 1 to 9. , complex metal halides (Li (1-d-e) ,Na (d) ,M' (e) ) 2Li( 1-z’) Me 3+ (1-u-p-q-r) Me 4+ (u) Me 2+ (p) Me 5+ (q ) Me 6+ (r)(Cl(1-y-w) Br (y) I (w )(6+u-p+2q+3r -z’) A solid ionically conductive material characterized by being represented by: 0 ≤ d ≤ 1; 0≦e<1; -3 ≤ z' < 3; M' includes at least one of K, Rb, and Cs. M 3+ is a rare earth element, In, Bi, Sc, Y, Al, Ga, or any of them Includes combinations. Me 4+ is Zr 4+ ,Hf 4+ ,Ti 4+ ,Sn 4+ ,Th 4+ ,Ge 4+ Or It is a combination of: Me 2+ is Mg 2+ ,Zn 2+ ,Ca 2+ ,Sr 2+ ,Ba 2+ ,Yb 2+ ,EU 2 + Or any combination thereof. Me 5+ Ta 5+ , Nb 5+ , W 5+ , Sb 5+ or a combination thereof. Me 6+ is W 6+ , Mo 6+ , or any combination thereof. 0<=w<=1; 0<=y<=1; -0.95 <z<0.95; 0<=u<0.95; 0<=p<0.95; 0<=q<0.95; and 0<=r<0.95. Embodiment 25.M 3+ But, Y 3+ , Gd 3+ , In 3+ , Er 3+ , La 3+ ,Sc. 3 + or any combination thereof, 3+ But, Y 3+ , Gd 3+ , In 3+ , Er 3+ , La 3+ ,Sc. 3+ or any combination thereof. 24 solid ionically conductive materials. Embodiment 26.M 4+ Zr 4+ , Hf 4+ , Ce 4+ , or a combination of these Including M 4+ Zr 4+ , Hf 4+ , Ce 4+ or a combination thereof 26. The solid, ionically conductive material of embodiment 24 or 25. Embodiment 27. The solid, ionically conductive material according to any one of embodiments 24 to 26. There p=0; q=0; r=0; u=0; or That combination. Embodiment 28. Embodiments 1 to 9 and 24 to 28, wherein k=2, 3, 4, or 5. 27. The solid, ionically conductive material according to any one of claims 27 to 27. Embodiment 29. The solid, ionically conductive material of any one of embodiments 1 to 28. Therefore, at least 10 mass ppm of halogenated metal halide based on the total weight of the complex metal halide Ammonium, at least 100 ppm, at least 500 ppm, at least 0.1 w t%, at least 0.3wt%, at least 0.5wt%, at least 0.8wt% or is a solid ionically conductive material containing at least 1 wt%. Embodiment 30. Ammonium is at most 20% by weight based on the total weight of the complex metal halide. wt%, at most 15wt%, at most 10wt%, at most 8wt%, at most 5wt %, or at most 3 wt. % of the solid ionic liquid according to any one of embodiments 1 to 29. Conductor material.
[0137] Embodiment 31. At most 0.5 wt% of the weight of the complex metal halide, at most At most 0.3 wt%, at most 0.1 wt%, at most 500 ppm, at most 300 ppm , at most 100ppm, at most 50ppm, at most 40ppm, at most 30ppm m, a total content of simple metal halides of at most 20 ppm or at most 10 ppm 31. The solid ion conductor material of any one of embodiments 1 to 30, further comprising: Embodiment 32: A small amount of simple metal halides is used relative to the total weight of complex metal halides. at least 0.2 ppm, at least 0.5 ppm, or at least 1 ppm, 32. The solid ionically conductive material according to claim 31. Embodiment 33. Simple metal halides include alkali metal halides, rare earth halides, 33. The solid-state imaging system of embodiment 31 or 32, comprising a hydroxybenzoate, ... Ionically conductive materials. Embodiment 34. Charge-neutral Me x N k is at least 0.0 ... 34. The method of any one of embodiments 1 to 33, including 0.1 ppm by weight and up to 10 ppm by weight. On conductive material. Embodiment 35. Based on the weight of the complex metal compound x , charge neutral M x N at least 0.1 35. The ion-containing composition of any one of embodiments 1 to 34, including up to 10 ppm by weight. Conductive material. Embodiment 36. At least 0.001 mS / cm, at least 0.01 mS / cm, At least 0.1mS / cm, at least 0.4mS / cm, at least 0.8mS / cm , at least 1.2 mS / cm, at least 1.8 mS / cm or at least 2.2 m 36. The solid ionic liquid of any one of embodiments 1 to 35, comprising an ionic conductivity in the bulk of 0.5 S / cm. Conductor material. Embodiment 37. Maximum 15 mS / cm, maximum 13 mS / cm, maximum 11 mS / cm, maximum 8mS / cm, up to 7.2mS / cm, or up to 6.2mS / cm ions in bulk 37. The solid ion conductor material of embodiment 36, comprising conductivity. Embodiment 38. The complex metal halide has an average particle size of at least 0.1 microns to 1 mm. 38. The solid ion conducting material according to any one of embodiments 1 to 37, which is in the form of a powder containing nanoparticles. sexual material. Embodiment 39. Any of embodiments 1 to 38, wherein the solid conductive material is single crystalline or polycrystalline. The solid ionically conductive material according to any one of claims 1 to 5. Embodiment 40. The solid ionically conductive material is a single crystal or <hkl>or <hklm>It is an oriented polycrystal having a crystal orientation represented by <hkl>or <hklm>of The ionic conductivity in one crystal orientation is higher than that in a different crystal orientation. 40. The solid, ionically conductive material of embodiment 39.
[0138] Embodiment 41. The solid ionically conductive material comprises: <100> and <001> Select from a group including 41. The solid, ionically conductive material of embodiment 39 or 40, having a crystallographic orientation as determined by Embodiment 42. Li4(NH2)3Cl, Li7(NH2)6Cl, Li2Br(NH 2) Li 13 [NH]6Cl, LiCl·NH3, LiBr·4NH3, or any of these 42. The solid ion conducting material of any one of the preceding embodiments, further comprising a combination of: sexual material. Embodiment 43. An embodiment further comprising NH3, NH4X, or a combination thereof 43. The solid, ionically conductive material according to any one of claims 1 to 42. Embodiment 44. The solid ionically conductive material according to any one of embodiments 1 to 43. , solid electrolyte layer. Embodiment 45. A solid, ionically conductive material according to any one of embodiments 1 to 43; and An electronically and ionically conductive material comprising a positive or negative electrode active material and, optionally, an electronically conductive additive. mixed layer. Embodiment 46. A solid-state lithium battery comprising the solid electrolyte layer of embodiment 44. Embodiment 47. A solid lithium battery comprising the electronic and ionic mixed conductive layer according to embodiment 45. battery. Embodiment 48.M 3-z (Me k+ ) f X 3-z+k*f Complex metal halogen represented by a solid electrolyte layer comprising a single crystal material containing an oxide; -3 ≤ z < 3; 2 ≤ k < 6; 0 ≤ f ≤ 1; M includes an alkali metal element. Me is a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, metallic elements, or any combination thereof; and X comprises a halogen; and Here, the single crystal material is a charge-neutral Me x N k , and M x N , x is the valence of N, and k is the valence of Me. Embodiment 49.M 3-z (Me k+ ) f X 3-z+k*f Orientation having a composition represented by A solid electrolyte layer comprising a crystalline material. -3 ≤ z < 3; 2 ≤ k < 6; 0 ≤ f ≤ 1; M includes an alkali metal element. Me is a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, metallic elements, or any combination thereof; and X includes a halogen. Embodiment 50. Embodiment 49, wherein the oriented crystalline material is an oriented ceramic or an oriented single crystal. The solid electrolyte layer according to claim 1.
[0139] Embodiment 51. The method of any one of embodiments 48 to 50, wherein M comprises at least one of Li and Na. 10. The solid electrolyte layer according to any one of claims 1 to 9. Embodiment 52. M is Li, or Li and at least one of Na, Cs, Rb, and K. 52. The solid electrolyte layer of any one of embodiments 48 to 51, comprising a combination of: Embodiment 53. The composition comprises (Li 1-d ,Na d )2Li 1-z Me k+ X 3+k-z 52. The solid electrolyte layer of any one of embodiments 47 to 51, wherein: 0≦d<1; -0.95 ≤ z <= 0.95; 2 ≤ k < 6; Me is a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, metallic elements, or any combination thereof; and X includes a halogen. Embodiment 54. Me is a rare earth element and optionally an alkaline earth metal element, Zn, Zr, H and one or more of Ti, Sn, Th, Ta, Nb, Mo, W, Sb, In, and Bi. The solid electrolyte layer according to any one of embodiments 47 to 53. Embodiment 55. Me is Y, Ce, Gd, Er, Zr, La, Yb, In, Mg, or 55. The method of claim 47, wherein the method comprises administering to the patient a therapeutically effective amount of the compound of the present invention. Body electrolyte layer. Embodiment 56. X is at least one of F, Cl, Br, and I, and optionally , -NH2 (amide), -(NH) 0.5 (imide), -OH (hydroxide), -BF4 group 56. Any one of embodiments 47 to 55, comprising an anionic group comprising The solid electrolyte layer according to claim 1. Embodiment 57. Me is Gd, Ce, Er, Yb, Zr, Y, or any of them. 56. The solid electrolyte layer of any one of embodiments 47 to 55, including combinations. Embodiment 58. Me is a metal oxide containing Gd and optionally at least one of Ce, Er, Y, and Zr. 56. The solid electrolyte layer of any one of embodiments 47 to 55, including one or more of: Embodiment 59. Any one of embodiments 47 to 55, wherein Me consists of Yb and Ce. The solid electrolyte layer described. Embodiment 60. Me is a metal selected from the group consisting of Y and optionally at least one of Zr, Ce, Er, and Gd. 56. The solid electrolyte layer of any one of embodiments 47 to 55, consisting of both a
[0140] Embodiment 61. The embodiment wherein the halogen is one of Cl, Br, I, and F. 61. A solid electrolyte layer according to any one of claims 47 to 60. Embodiment 62. The halogens consist of at least two of Cl, Br, I, and F. 62. The solid electrolyte layer of any one of embodiments 47 to 61, wherein Embodiment 63. Any of Embodiments 47 to 62, wherein the halogen consists of Cl, Br, and I. 10. The solid electrolyte layer according to claim 9, wherein the solid electrolyte layer is a polyimide. Embodiment 64. The composition is Li 3-z RE k+ X 3-z+k where RE is the rare earth element 64. Any one of embodiments 47 to 63, comprising: The solid electrolyte layer according to any one of the preceding claims. Embodiment 65. Any one of embodiments 47 to 64, wherein k=3 or 4 or 5. The solid electrolyte layer according to claim 1. Embodiment 66. The composition comprises (Li (1-d) ,Na (d) )2Li (1-z) Me 3+ (1-u-p-q-r) Me 4+ (u) Me 2+ (p) Me 5+ (q) Me 6+ (r) (Cl (1-y-w) Br (y) I (w))(6+u-p+2q+3r-z)で Represented 66. The solid electrolyte layer of any one of embodiments 47 to 65, wherein: 0 <d<=1; -0.95 ≤ z <= 0.95; 0<=u<0.95; 0<=p<0.95; 0<=q<0.95; 0<=r<0.95; M 3+ Contains rare earth elements. Me 4+ is Zr 4+ , Hf 4+ , Ti 4+ , Sn 4+ , Th 4+ , or any of them It's quite a combination. Me 2+ is Mg 2+ ,Zn 2+ ,Ca 2+ ,Sr 2+ ,Ba 2+ ,Yb 2+ ,EU 2 + Or any combination thereof. Me 5+ Ta 5+ , Nb 5+ , W 5+ , Sb 5+ or a combination thereof. Me 6+ But, W 6+ ; 0<=y<=1; and w<=1. Embodiment 67.M 3+ But, Y 3+ , Gd 3+ , In 3+ , Er 3+ , La 3+ ,or Any combination thereof, including M 3+ But, Y 3+ , Gd 3+ , In 3+ , Er 3+ , La 3+ 67. The solid electrolyte layer of embodiment 66, comprising: . Embodiment 68.M 4+ Zr 4+ , Ce 4+ , or a combination thereof, 4 + Zr 4+ , Ce 4+ 68. In any one of embodiments 66 to 67, The solid electrolyte layer described. Embodiment 69. A solid electrolyte layer according to any one of embodiments 63 to 68. p=0; q=0; u=0; or That combination. Embodiment 70. The solid electrolyte layer of any one of embodiments 47 to 69, A solid electrolyte layer, wherein z≦0.5, z≦0.3, or z≦0.2.
[0141] Embodiment 71. A solid electrolyte layer according to any one of embodiments 47 to 70, comprising: 71. Any of embodiments 47 to 70, wherein d≧0.01 or d≧0.05 or d≧0.1. The solid electrolyte layer according to any one of claims 1 to 4. Embodiment 72. A solid electrolyte layer according to any one of embodiments 47 to 71, d ≤ 0.8 or d ≤ 0.5. Embodiment 73. A solid electrolyte layer according to any one of embodiments 47 to 72, comprising: The crystalline material may contain at most 0.5 wt. % of the total weight of the crystalline material, and at most 0.2 wt. t%, at most 0.1wt%, at most 500ppm, at most 200ppm, at most 100 ppm, or at most 50 ppm total impurity content. Embodiment 74. The impurities are rare earth halides, alkali halides, charge-neutral Me x N k , charge neutral M x N, or any combination thereof. Solid electrolyte layer. Embodiment 75. The total content of impurities is at least 2 ppm, at least 5 ppm, or at least 10 ppm of crystalline material; 75. The solid electrolyte layer of any one of embodiments 47 to 74. Embodiment 76. The crystalline material is at least 0. 1 ppm by mass, up to 10 ppm by mass of charge-neutral Me x N k Embodiments 47 to 75, including 10. The solid electrolyte layer according to claim 9, wherein the first and second electrodes are electrically connected to each other. Embodiment 77. The crystalline material is at least 0.1 times the weight of the complex metal halide. ppm by mass, up to 10 ppm by mass charge neutral M x Any of embodiments 47 to 76, including N. 10. The solid electrolyte layer according to claim 1, Embodiment 78. The crystalline material is Li4(NH2)3Cl, Li7(NH2)6Cl, Li 2Br(NH2), Li 13 [NH]6Cl, LiCl-NH3, LiBr-4NH3, 78. The solid electrolytic composition of any one of embodiments 47 to 77, including a sol- id electrolyte, ... quality layer. Embodiment 79. The crystalline material comprises NH3, NH4X, or a combination thereof. 79. A solid electrolyte layer according to any one of embodiments 47 to 78. Embodiment 80. The crystalline material has a conductivity of at least 0.01 mS / cm at 22°C and at least 0. 1mS / cm, at least 0.2mS / cm, at least 0.4mS / cm, at least 0.5mS / cm, at least 0.8mS / cm, at least 1.2mS / cm, at least 79. Any one of embodiments 47 to 79, including a bulk ionic conductivity of 1.8 mS / cm. In the solid electrolyte layer described above, the crystal has a valence of at least 0.01 eV to 0.5 eV. The crystal has an activation energy of at least 0.01 eV. 8 mS / cm, or less at 22° C. At least 2.2 mS / cm, and activation energies in the range of 0.01 eV and 0.5 eV Ghee or crystalline materials: up to 15mS / cm, up to 11mS / cm, up to 9mS / cm , ionic conductivity up to 8mS / cm, up to 7.2mS / cm or up to 6.2mS / cm Examples of crystalline materials include:
[0142] Embodiment 81. Having a thickness, <hkl>or <hklm>Extends in the crystallographic direction , <hkl>or <hklm>The ionic conductivity in the crystallographic orientation of the 81. The solid electrolyte according to any one of embodiments 1 to 80, wherein the ionic conductivity at the quality layer. Embodiment 82. The crystallographic direction is <100> , <001> , and <010> A group containing 82. The solid electrolyte layer of embodiment 81, wherein the solid electrolyte layer is selected from: Embodiment 83. Any one of embodiments 47 to 82, wherein the single crystal material is in sheet form. The solid electrolyte layer according to claim 1. Embodiment 84. Any of embodiments 1 to 83, wherein the thickness is 5 microns to 500 microns. 1. The solid electrolyte layer according to any one of the preceding items. Embodiment 85. A process for forming a solid, ionically conductive material, comprising: (NH4) n Me k+ 3+k (NH4) n Me k+ 3+k Form The step of: 0;Me includes rare earth elements, Zr, or a combination thereof, and X is one or more halogens. . Embodiment 86. (NH4) n Me k+ 3+k and MX. 86. The process of embodiment 85, wherein M comprises an alkali metal. Embodiment 87. (NH4) n Me k+ X 3+k
[0023] In some embodiments, the method further comprises: 85 or 86. Embodiment 88.M 3-z Me k+ X 3-z+k , where -3≦z<3;2≦k<6;M contains at least one of Li and Na, and the solid ionically conductive material is Complex metal halides containing a total content of impurities of up to 0.5 wt% based on the weight of the material 88. The process of any one of embodiments 85 to 87, further comprising: Embodiment 89. The impurity is Me k+ X k , MX, or a combination thereof. 89. The process of embodiment 88. Embodiment 90. The method further comprising growing a crystal comprising a complex metal halide. 90. The process of any one of embodiments 86 to 89.
[0143] Embodiment 91. <010> , <100> , and <001> A crystal selected from the group comprising 91. Any of embodiments 85 to 90, further comprising forming an oriented crystalline material comprising an optically oriented 10. The process of any one of claims 1 to 9. Embodiment 92. The method further comprising growing a crystal from the melt, wherein the melt is a complex metal halide. 92. The process of embodiment 90 or 91, comprising a nitride and optionally a dopant material. Embodiment 93. Any of embodiments 85 to 92, wherein the ion-conducting material is polycrystalline. The process described in one. Embodiment 94. The ion-conducting material is at most 0.5 wt. by weight of the ion-conducting material. % charge-neutral Me x N k 94. The method of any one of embodiments 85 to 93, comprising the step of: process. Embodiment 95: The ion conductive material is less in mass ratio to the weight of the ion conductive material. At most 0.1 ppm, at most 10 ppm x N k From embodiment 85, containing the content of 94. The process according to any one of claims 94 to 94. Embodiment 96. The ion-conducting material is at most 0.5 wt. % charge neutral M x 96. The process according to any one of embodiments 85 to 95, comprising a content of N. Seth. Embodiment 97: The ion conductive material is less in mass ratio to the weight of the ion conductive material. At most 0.1 ppm, at most 10 ppm of charge-neutral M x Embodiment 85, including the content of N 96. The process according to any one of claims 1 to 96. Embodiment 98. The ion-conducting material is Li4(NH2)3Cl, Li7(NH2)6C l, Li2Br(NH2), Li 13 [NH]6Cl, LiCl-NH3, LiBr-4 NH3, or a combination thereof. 10. The process according to any one of the preceding claims. Embodiment 99. The ion-conducting material is a material containing NH3, NH4X, or a combination thereof. 98. The process of any one of embodiments 85 to 97, further comprising:
[0144] example Example 1 Samples 1 to 30 were prepared with the compositions shown in Table 1. Table 1 shows the impurities of simple metal halides. The content of each impurity is listed, and each impurity phase is identified by a characteristic diffraction peak corresponding to the parasitic phase. Detection by XRD analysis combined with Rietveld refinement for quantitative analysis by presence It was done.
[0145] All samples had a metal nitride content of up to 10 ppm. Samples 1, 2, 4-6, 15, 17, and 30 were made by pressing ceramic pellets and drying them. The pellets were heated under dry, inert conditions. Sample 6 was prepared according to the wet ammonium route described in the embodiment of this specification. The pellets were molded using a one-step molding process described in
[2012] . The pellets ranged in size from 5 to 13 mm (diameter ) × 0.5 to 4 mm (thickness). Samples 8 to 14 and Samples 18 to 29 were Samples 20 and 21 were sliced from single crystals formed according to the embodiment. The formation of 23 involves the addition of LiC as a starting material for crystal growth of an anion-substituted compound. The Li salt, LiBr salt, and LiI salt were used, respectively.
[0146] The ionic conductivity of the sample was measured by electrochemical impedance spectroscopy using a gold block electrode. , AC frequency 3MHz-10Hz, peak-to-peak sine wave AC voltage signal 10~5 The measurements were taken at 0 mV and room temperature (approximately 22°C).
[0147] The ionic conductivities of bulk crystals of samples 1, 2, 4-6, 15, 17, and 30 are included in Table 1. The bulk grain conductivity signature appears at the highest frequency and is associated with the lowest value of the double layer capacitance. Therefore, the conductivity contribution from the bulk grains can be separated from the grain boundaries and electrode contacts. Cut.
[0148] In sample 3, both directions A and B show the maximum thermal conductivity and / or does not correspond to the direction of ionic conductivity. When sliced along direction A, random A ceramic sample with crystal grains of the crystal orientation A was obtained. The direction A is determined by the vector a. and a = α * <100> +β * <010> and -1.0<α<1.0 and When sliced in the B direction, the crystal orientation is <001> distribution close to Oriented ceramic samples with different orientations were obtained.
[0149] [Table 1] [Table 1]
[0150] Example 2 A polycrystalline block of Li3YB6 was formed into a cylindrical shape measuring 7cm x 10cm. The block is composed of mm to cm sized single crystals densely arranged in layers like mica. The bulk ionic conductivity was measured on a small piece cut from the center of the rock. The specimen was polished into a parallel plate sample with a thickness of approximately 0.7 mm, and the impedance was measured in the same manner as in Example 1. The measured values were approximately 0.5 or 2.5 mS / cm, depending on the sample orientation chosen. RD analysis confirmed that the two samples had different crystallographic orientations.
[0151] crystallographic direction <100> The first one has mainly (80% or more) crystal grains oriented approximately along The sample with the highest thermal conductivity also exhibited higher ionic conductivity. The second sample exhibited <0 Randomly oriented grains with crystallographic orientations belonging to planes perpendicular to the 01> direction were observed. This is proof.
[0152] Example 3 The pure crystalline material was ground using an automatic mortar and pestle grinder. High-energy ball milling preserves the purity of the material. As shown by the appearance of small signals of simple halides in XRD analysis, Partial decomposition of the pure material was observed. The conductivity of the decomposed powder was significantly higher than that of the pure powder and the oriented crystallites. The value was lower than that of ceramic.
[0153] Example 4 [Table 4]
[0154] High-energy ball milling synthesis is not only the synthesis reaction of the main complex metal halide phases. It is important to note that the decomposition reaction can occur in parallel without the need for a high-energy The holomilling synthesis results in a predominant Li3YX6 phase compared to the process of the present embodiment. The content of simple compounds such as LiX and YX3 present as impurities in the vicinity of It may be higher.
[0155] Also, starting from oxide (Y2O3) or carbonate materials (Li2CO3), When ammonium halide was added in a solid-state reaction at atmospheric pressure, a single phase of Li3YX6 was synthesized. It is noted that rare earth metals (i.e., Y in the Li3YX6 example) There are at least two possible chemical reactions that can occur in the conversion of fluorine to its halide compound. The key reaction results in the synthesis of YX3, which can further react to form the Li3YX6 phase. A second reaction can result in the formation of YOX. YOX is stable. It is a compound that may be present as an impurity in the final product Li3YX6.
[0156] Example 5 Additional samples were prepared. Sample 35 was prepared by welding a stoichiometric mixture of LiBr and YBr. The reaction mixture was placed in a quartz ampoule and heated to 650°C under vacuum. Then, a soak time of up to 1 hour at 650°C is required to dissolve the reaction products into a self-flux. After that, the temperature of the quartz ampoule was quickly lowered (in 2 to 3 minutes) to 400°C. This helped to minimize the partial decomposition of the mismatched Li3YBr6 phase. The temperature of the English ampoule was gradually lowered to room temperature at a rate of 50-100°C / hour.
[0157] Samples 36 and 37 were synthesized according to embodiments herein and optionally contained ammonium. The amount of residual ammonium was determined by the amount of charge that was released when the ammonium halide was completely sublimated. The melting point of the sample was estimated by post-heating the compound to its melting point. The ionic conductivity in the film was measured in the same manner as described in Example 1. [Table 5]
[0158] Benefits, other advantages, and solutions to problems have been described above with regard to specific embodiments. However, benefits, advantages, solutions to problems, and any benefits, advantages, or solutions Any feature(s) that may cause or make more pronounced any or all These claims should not be construed as key, essential, or essential features of the present invention. Therefore, a reference to a material containing one or more ingredients means that the material consists essentially of one or more of the identified ingredients. "Consisting essentially of" can be interpreted as including at least one embodiment that is The term "materials" includes those materials specified, and minor amounts that do not significantly change the properties of the material. "compositions" shall be interpreted to include compositions excluding all other materials other than the above (e.g., impurity content). Additionally or alternatively, in certain non-limiting embodiments, the compounds identified herein may be Any of the compositions described may be essentially free of materials not expressly disclosed. Embodiments herein include ranges of content of particular components in materials, and the ranges of content of particular components in a given material. It will be understood that the content of ingredients totals 100%.
[0159] The specification and illustrations of the embodiments set forth herein are provided to provide a general understanding of the structure of the various embodiments. The present specification and illustrations are intended to provide a thorough understanding of the structures or The method provides a comprehensive and comprehensive description of all of the elements and features of the apparatus and systems that use the method. The separate embodiments may also be combined in a single embodiment. Conversely, the present invention may be provided in combination with other embodiments, which may, for brevity, be described in the context of a single embodiment. The various features described may also be provided separately or in any subcombination. Furthermore, references to values stated within ranges include each and every value within that range. Many other embodiments may become apparent to those skilled in the art only after reading this specification. Other embodiments may include structural and logical substitutions and variations without departing from the scope of this disclosure. may be used and derived from this disclosure, as may other modifications. Accordingly, the present disclosure is to be regarded as illustrative and not restrictive.< / hklm> < / hkl> < / hklm> < / hkl> < / hklm> < / hkl> < / hklm> < / hkl> < / hkl> < / hklm> < / hkl>
Claims
1. 1. A solid, ionically conductive material comprising a complex metal halide material, The complex metal halide material is (Li 1-d-e , Na d , M' e ) 2 Li 1-z’ (Me k+ ) f X 3+k*f-z’ is represented by: 2≦k≦6; 0≦f≦1; 0<d≦1; 0≦e<1; 0≦(d+e)<1, except that (d+e)>0 when f=0; −1≦z′<1; M' is one or more alkali metals other than Li and Na; Me comprises a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or a combination thereof; X comprises a halogen; 1. A solid, ionically conductive material, wherein said complex metal halide material comprises a total content of LiX phases of at most 3 wt. % based on the total weight of said complex metal halide material.
2. (Li 1-d-e , Na d , M' e ) 2 Li 1-z’ (Me k+ ) f X 3+k*f-z’ A solid, ionically conductive material comprising a crystallographically oriented ceramic material comprising a complex metal halide material represented by: 2≦k≦6; 0≦d≦1; 0≦e<1; 0≦(d+e)<1, except that (d+e)>0 when f=0; −1≦z′<1; M' is one or more alkali metals other than Li and Na; Me comprises a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or a combination thereof; X comprises a halogen, including at least one of Cl or Br; A solid ionically conductive material, wherein the crystal grains of the composite metal halide material are oriented in a crystallographic orientation represented by <HKL> or <HKLM>, and the ionic conductivity in the crystallographic orientation of <HKL> or <HKLM> is higher than the ionic conductivity in a different crystallographic orientation.
3. A solid ionically conductive material comprising a crystallographically oriented ceramic material including a complex metal halide material represented by (Li1-de, Nad, M'e)2Li1-z'(Mek+)fX3+k*f-z', 2≦k≦6; 0≦d≦1; 0≦e<1; 0≦(d+e)<1, except that (d+e)>0 when f=0; −1≦z′<1; M' is one or more alkali metals other than Li and Na; Me comprises a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or a combination thereof; X comprises a halogen, including at least one of Cl or Br; A solid, ionically conductive material, wherein more than 80% of the crystal grains of said crystallographically oriented ceramic material are oriented in a crystallographic orientation represented by <HKL> or <HKLM>, and wherein the ionic conductivity in said crystallographic orientation of <HKL> or <HKLM> is higher than the ionic conductivity in a different crystallographic orientation.
4. The complex metal halide material is a charge-neutral Me x N k Or M x 4. The solid, ionically conductive material of claim 1 , comprising at least one of N, x being the valence of nitrogen N, and k being the valence of Me.
5. 5. The solid, ionically conductive material of any one of claims 1 to 4, wherein the halogen is one or more of Cl and Br.
6. 6. The solid, ionically conductive material of any one of claims 1 to 5, wherein Li constitutes at least 50 mol % of the sum of Li, Na, and M'.
7. 7. The solid, ionically conductive material of any one of claims 1 to 6, wherein z' is from -0.95 to 0.95 and Na constitutes up to 40 mol % of the sum of Li, Na, and M'.
8. The solid, ionically conductive material of claim 1, wherein e=0.
9. 9. The solid, ionically conductive material of any one of claims 1 to 8, wherein Me comprises Y, Ce, Gd, Er, Zr, Hf, La, Sn, Yb, In, Mg, Zn or combinations thereof.
10. 10. The solid, ionically conductive material of any one of claims 1 to 9, wherein X comprises Cl and Br.
11. 11. The solid, ionically conductive material of any one of claims 1 to 10, wherein the complex metal halide material comprises a total content of simple metal halides of at most 2 wt% based on the weight of the complex metal halide material, the simple metal halides comprising alkali metal halides, rare earth halides, or any combination thereof.
12. 12. An electrolyte comprising the solid, ionically conductive material of any one of claims 1 to 11.
13. 12. A mixed ionic and electronic conducting layer comprising the solid ionically conducting material according to claim 1 and an electronically conducting material.
14. 12. A composite layer comprising the solid, ionically conductive material of any one of claims 1 to 11 and an organic material.
15. 4. A layer comprising the solid, ionically conductive material of claim 2 or 3, the layer comprising an electrolyte, a composite layer, a mixed ionic and electronic conducting layer, or any combination thereof, and the crystallographically oriented ceramic material is oriented through the thickness of the layer.
Citation Information
Patent Citations
Lithium secondary battery solid electrolyte material, electrode and battery
JP2022531271A
Solid electrolyte material, and cell
WO2018025582A1
Solid electrolyte material and battery
WO2019135317A1
Solid electrolyte material and battery
WO2019135318A1
Solid electrolyte material and battery
WO2019135347A1